AN ANALYSIS OF ILLOCUTIONARY ACTS ON PRESIDENT JOE BIDEN’S INAUGURAL SPEECH - Hidaiyat, Muhammad; Weda, Sukardi (Journal of English Literature and Linguistic Studies, 2025)
The concept of speech act holds significant importance in the realm of communication maintenance. The text encompasses both substantive information and directives for an individual to undertake a certain task. This study aimed to explore the concept of speech act. The objective of this study is to investigate the type of illocutionary act and the semantic significance of illocutionary acts in President Joe Biden's Inaugural Speech. The research methodology employed in this study is a descriptive qualitative approach. The researcher employed the documentation approach as a means of data collection. The data consist of speech acts extracted from the speeches delivered by President Joe Biden. Based on the examination of the data, the researcher identified five distinct categories of illocutionary acts, as outlined in Searle's thesis. There are a total of 14 instances of assertive data, 4 instances of directive data, 9 instances of commissive data, 7 instances of expressive data, and 3 instances of declarative data.